2020
DOI: 10.1136/svn-2020-000456
|View full text |Cite
|
Sign up to set email alerts
|

Donning and doffing of personal protective equipment protocol and key points of nursing care for patients with COVID-19 in ICU

Abstract: Coronavirus pandemic is the most important public health event in the world currently. Patients with coronavirus disease 2019 (COVID-19) in a critical state are at risk of progressing rapidly into many serve complications; they require a high level of care from ICU nurses. How to avoid the virus to infect health care worker is also a critical issue. Based on the summarized experience of Chinese health workers, literature review and clinical practice, this article introduced donning and doffing of personal prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 34 publications
2
14
0
11
Order By: Relevance
“…Our results coincide with previous studies that show the nurses' concern to optimize the time dedicated to caring for patients with COVID-19. Thus, there is a need to limit exposure to the virus while maintaining quality care (Gao et al, 2020;Ye et al, 2020;Yuan et al, 2020). Omess et al (2021) reported that they applied a novel Warm Zone Model during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results coincide with previous studies that show the nurses' concern to optimize the time dedicated to caring for patients with COVID-19. Thus, there is a need to limit exposure to the virus while maintaining quality care (Gao et al, 2020;Ye et al, 2020;Yuan et al, 2020). Omess et al (2021) reported that they applied a novel Warm Zone Model during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous initiatives have emerged to improve and optimize recommendations in the fight against the pandemic, in the designated areas of PPE donning and doffing in risk zones, (CDC COVID-19 Response Team, 2020; Yuan et al,2020) together with restructuring and planning nurses' work and the spaces within the units (Omess et al,2021;Ye et al,2020). These strategies can be difficult and time consuming to adhere to in practice.…”
Section: Introductionmentioning
confidence: 99%
“…The year 2020 may be considered as the "year of Corona" ( 1 ). The Coronavirus disease 2019 (COVID-19) is considered a challenge for the health systems around the world ( 2 , 3 ). The challenge of caring for COVID-19 patients ( 4 ) has imposed a substantial burden on health care ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Este déficit no fue compensado con un seguimiento y/o tutorización del personal sanitario en los momentos considerados críticos (puesta y retirada del EPI), ya que menos de la cuarta parte de los encuestados indica que tuvo supervisión en estas situaciones y casi la mitad indica que no percibió apoyo institucional. Tal y como muestran los estudios de Wang y col 10 , Yuan y col 11 y Parush y col 12 , las medidas formativas, los protocolos bien establecidos y las medidas de auditoría y supervisión disminuyen considerablemente el riesgo de contagio entre los profesionales sanitarios. En nuestro estudio, el déficit de formación y contagio por SARS-CoV-2 muestran una relación relevante, ya que los profesionales que recibieron formación tuvieron tasas de contagio significativamente inferiores en comparación al grupo de profesionales que no recibió ninguna formación.…”
Section: A H E a D O F P R I N Tunclassified